2012
DOI: 10.1097/mbc.0b013e3283573a42
|View full text |Cite
|
Sign up to set email alerts
|

Soluble CD163 in young sickle cell disease patients and their trait siblings

Abstract: CD163 is expressed on cells of monocyte-macrophage lineage and is the main hemoglobin-haptoglobin receptor. Inflammation and monocyte activation are predisposing factors to vaso-occlusion and pulmonary hypertension, which are serious complications in sickle cell disease (SCD). Siblings of SCD patients may have the same pathophysiology without displaying symptoms. We assessed soluble CD163 (sCD163) levels in 60 children with SCD and 30 sickle cell trait (SCT) siblings compared with 30 healthy controls as a pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Nakayama et al found that in patients with scleroderma and elevated serum soluble CD163 (sCD163) levels, 70% of patients had an elevated RVSP on echo versus 28% of patients with normal levels (54). In patients with sickle cell disease and PH, soluble sCD163 levels were over twice that of sickle cell patients without PH (55). …”
Section: Discussionmentioning
confidence: 99%
“…Nakayama et al found that in patients with scleroderma and elevated serum soluble CD163 (sCD163) levels, 70% of patients had an elevated RVSP on echo versus 28% of patients with normal levels (54). In patients with sickle cell disease and PH, soluble sCD163 levels were over twice that of sickle cell patients without PH (55). …”
Section: Discussionmentioning
confidence: 99%
“…HIV-infected individuals also have elevated levels of inflammatory cytokines such as interleukin-1, interleukin-10, interleukin-12p40, interferon γ produced protein 10, interferon γ, as well as markers of cellular activation [soluble CD25 (sCD25) [8], soluble CD14 (sCD14), soluble tumor necrosis factor 2 (sTNFR-2), soluble vascular cell adhesion molecule 1 (sVCAM-1), and soluble CD163 (sCD163)] [7,9,10]. …”
Section: Introductionmentioning
confidence: 99%
“…Increased levels of circulating CFH have also been shown in the SU/hypoxia rat model of PAH and correlate with disease severity 33,34 . Moreover, populations at risk for developing pulmonary hypertension have abnormalities in hemoglobin processing proteins 17,18 . Hemoglobin infusion in animal models leads to pulmonary vascular injury which is mitigated by concomitant infusion of the CFH scavenger haptoglobin 13,15,16,35,36 .…”
Section: Discussionmentioning
confidence: 99%
“…33,34 Moreover, populations at risk for developing pulmonary hypertension have abnormalities in hemoglobin processing proteins. 17,18 Hemoglobin infusion in animal models leads to pulmonary vascular injury which is mitigated by concomitant infusion of the CFH scavenger haptoglobin. 13,15,16,35,36 Collectively, these studies suggest CFH generation and incomplete metabolism are common features of pulmonary vascular dysfunction that may be modifiable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation